The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/fwb.12070
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of parthenogenetic flatworm populations with occasional sex

Abstract: Summary 1. Sexual populations are expected to perform better in fluctuating environments than asexuals because recombination provides the potential to adapt to changing environments due to increased genetic variation. Nevertheless, some asexual species show comparably high levels of genotypic diversity. Such diversity might be achieved through gene flow between coexisting sexual and asexual populations or through sexual events within asexual populations. 2. Evidence for occasional sex in the flatworm Schmidtea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 84 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…Earlier studies in other sexual/asexual systems have shown that the frequency of sexual reproduction varies among natural populations and that the genetic signature of sexual reproduction can be seen in many predominately asexual populations (Michiels et al ., ; Bruvo et al ., ; Allen & Lynch, ; Sánchez Navarro et al ., ). However, direct comparisons of temporal variation in sexual frequency in mixed populations remain rare.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies in other sexual/asexual systems have shown that the frequency of sexual reproduction varies among natural populations and that the genetic signature of sexual reproduction can be seen in many predominately asexual populations (Michiels et al ., ; Bruvo et al ., ; Allen & Lynch, ; Sánchez Navarro et al ., ). However, direct comparisons of temporal variation in sexual frequency in mixed populations remain rare.…”
Section: Discussionmentioning
confidence: 97%
“…In some cases, such as found in the planarian flatworm, Schmidtea polychroa , polyploid individuals can produce viable sperm that may lead to rare sexual processes (Sánchez‐Navarro et al . ). As asexually reproducing plants and animals often have uneven ploidy levels (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…In the animal kingdom, the majority of polyploid invertebrates and reptiles reproduce asexually, and it has been estimated that 99% of apomictic plant species are polyploids (Suomalainen et al 1987). In some cases, such as found in the planarian flatworm, Schmidtea polychroa, polyploid individuals can produce viable sperm that may lead to rare sexual processes (S anchez-Navarro et al 2013). As asexually reproducing plants and animals often have uneven ploidy levels (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Second, parthenogenetic forms also harbor more infections by a presumed parasitic amoeboid protozoan, which is in some respects consistent with the Red Queen hypothesis that predicts sexuality protects against parasites, though in this case the costs of infection (required for the hypothesis to work) are unclear (Michiels et al, ). Subsequent efforts have focused on explaining the maintenance of both sexual and parthenogenetic forms, with phylogeographic and experimental evidence indicating that hybridization between the two occurs, as does genetic exchange between parthenogenetic individuals via various mechanisms that lead to the occasional retention of paternal chromosomes and exclusion of maternal chromosomes, and frequently involve transitions in ploidy (Pongratz et al, ; D'Souza et al, ; Sánchez Navarro and Jokela, ). This may help to maintain genetic diversity in parthenogens and explain their persistence.…”
Section: Lifestyle Choices Affecting Flatworm Reproductionmentioning
confidence: 99%